40AR-39AR AGE OF SIBERIAN BASALTIC VOLCANISM - Venkatesan T.R.; Kumar A.; Gopalan K.; Al'mukhamedov A.I. (My University, 1997)
Five of six samples representing the entire stratigraphic sequence (∼3700 m thick) of basaltic flows in the Noril'sk section in the northwestern part of Siberian flood basalt province, Russia yield 40Ar–39Ar plateau ages between 248.3±1.7 Ma and 246.9±2.5 Ma relative to an age of 520.4 Ma for the hornblende standard, MMhb-1. These results clarify some discrepancies in existing data and confirm that eruption of the bulk of Siberian basalts was close to 248 Ma and possibly lasted less than 2 Ma. Although the violence of this volcanism may have caused the massive extinctions at the Permo–Triassic boundary, the onset of changes across this boundary seems to have been distinctly earlier.
Keywords: Triassic; Permian; Mesozoic::Triassic; Палеозой::Пермская; Paleozoic::Permian; Мезозой::Триасовая